Assessment of risks on a territorial scale for archaeological sites in İzmir. Issue 6 (18th August 2018) - Yıldırım Esen, Sibel; Bilgin Altınöz, Ayşe Güliz
ABSTRACT: This article focuses on natural, institutional, and human factors threatening archaeological sites. A methodology is developed for assessing risks to multiple assets on a territorial scale. The methodology consists of hazard assessment, vulnerability assessment, and risk assessment. Hazard assessment involves identifying hazard exposure areas and measuring the frequency and intensity of each hazard. Vulnerability assessment incorporates examining physical, managerial, and contextual vulnerabilities of structures and remains. Geographical information systems are utilised for producing hazard, vulnerability, and risk maps. An overall picture of risks for an entire territory allows decision-makers to make informed decisions at an upstream level to limit further degradation and ensure the preservation of archaeological assets. The methodology was tested by conducting a comprehensive study in İzmir (Turkey), where 229 archaeological sites located in 21 metropolitan districts were studied. The proposed approach provides the promise of applicability across a range of historic environments.